2015
DOI: 10.3892/mmr.2015.3694
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer stem cell and chemoresistant colorectal cancer cell phenotypes and increased sensitivity to Notch pathway inhibitor

Abstract: Colorectal cancer stem cells (Co-CSCs) are a small subpopulation of tumor cells which have been proposed to be tumor-initiating cells in colorectal cancer (CRC) and to be implicated in resistance to standard chemotherapy. Chemoresistance is a common problem in the clinic. However, the interrelation between Co-CSCs and chemoresistant cells has yet to be elucidated. The present study investigated the Co-CSC phenotype in colonospheres and chemoresistant CRC cell lines and aimed to identify targets for therapy. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…Here, we demonstrate that acquired endocrine resistance potentiates sensitivity of the CSC-like compartment to TRAIL in primary-derived breast cancer samples, and that this significantly correlates with a reduction in c-FLIP levels. These observations are particularly significant given that CSCs have been demonstrated to evade conventional chemotherapy agents and potentially endocrine agents, either due to cell quiescence, through the prevention of drug uptake or modulation of intracellular signaling (18,21,(61)(62)(63). Targeted therapies that initiate cell death through cell surface receptors circumvent these resistance mechanisms and therefore may prove to be a more effective strategy for targeting CSCs (64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate that acquired endocrine resistance potentiates sensitivity of the CSC-like compartment to TRAIL in primary-derived breast cancer samples, and that this significantly correlates with a reduction in c-FLIP levels. These observations are particularly significant given that CSCs have been demonstrated to evade conventional chemotherapy agents and potentially endocrine agents, either due to cell quiescence, through the prevention of drug uptake or modulation of intracellular signaling (18,21,(61)(62)(63). Targeted therapies that initiate cell death through cell surface receptors circumvent these resistance mechanisms and therefore may prove to be a more effective strategy for targeting CSCs (64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that ovarian CSC contribute to apoptosis inhibition and EMT phenotypes from the activation of the PI3K/Akt signaling pathway, [31] MAPK signaling pathway, and Wnt signaling pathway, [43] eventually leading to drug resistance. Signaling pathway is complex, and its targeting drug efficacy still remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced therapeutic resistance has been attributed to CSCs [80,8287], which subsequently leads to increased tumor growth, invasion, and relapse. A common contributor to therapeutic resistance is enhanced DNA damage response.…”
Section: Therapy-resistant Cscs In Disease Relapsementioning
confidence: 99%